Where to find what : a handbook to reference service - Hillard, James M., 1920-; Easter, Bethany J. (Lanham, Md. : Scarecrow Press, 2000)
Presents an annotated listing of reference books, most of which can be found in medium- to large-sized public libraries and small academic libraries; grouped by topic.
Includes bibliographical references.
Professional
Keywords: Reference books -- Bibliography; Reference books -- Bibliography